2017
DOI: 10.1002/psp.2118
|View full text |Cite
|
Sign up to set email alerts
|

Place, kinship, and employment

Abstract: This study explores the magnitude and composition of kinship ties at Swedish workplaces. By analysing official register data and illustrating findings from interviews with HR personnel at different workplaces, the following questions are discussed: How much kinship concentration is there today on the labour market in a modern Western society such as Sweden? How is the kin-based selection of workplace members structured by place? The study is based on an analysis of individually connected register information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Despite the ambiguity regarding the role of family involvement in business, kinship ties still constitute an important part of the recruitment process. Although a systematic cross-country mapping of family involvement in business is missing, family co-occurrence constitutes about 14% of all employment in Sweden (Holm, Westin, & Haugen, 2017). This finding supports the notion that meritocracy in the labour market co-exists with other types of hiring practices (Adjei, 2018), such as nepotism.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Despite the ambiguity regarding the role of family involvement in business, kinship ties still constitute an important part of the recruitment process. Although a systematic cross-country mapping of family involvement in business is missing, family co-occurrence constitutes about 14% of all employment in Sweden (Holm, Westin, & Haugen, 2017). This finding supports the notion that meritocracy in the labour market co-exists with other types of hiring practices (Adjei, 2018), such as nepotism.…”
Section: Introductionsupporting
confidence: 63%
“…Therefore, it is reasonable to expect that in smaller regions, stronger and more trustful familial relationships are likely to be found in firms. Supporting this argument, Holm et al (2017) found low levels of kinship density in workplaces in Sweden's metropolitan regions, somewhat high levels in intermediate regions (urban regions), and higher levels in remote and sparsely populated areas (rural or small regions). They further showed that kinship density decreases with rising education levels, which means that workers with low education are over-represented in workplaces with high kinship density, a phenomenon that is likely highly associated with smaller and/or rural regions.…”
Section: Literature Review: Family Co-occurrence and Firm Productivitymentioning
confidence: 85%
“…Prior studies have reported that family co-occurrence is relatively more common in smaller regions compared to larger regions (Adjei, Eriksson, and Lindgren 2016;Holm, Westin, and Haugen 2017). Therefore, the contingency effects of the family on skill variety ought to be an important policy focus for regional planning.…”
Section: Moderating Effects Of Entrepreneurial Family Relationships Omentioning
confidence: 99%
“…Good organisational climate, which manifests as individual perception of the working environment, is vitally important for the smooth operation of organisations (Parker et al, 2003;Alwaheeb, 2020;Beus et al, 2020). Nevertheless, evidently, it is impossible to avoid work with relatives and the influence related to this during recruitment (Holm et al, 2017); therefore, these processes must be monitored, and the ways must be sought to reduce the negative impact (Horak, 2018). Neill et al (2019) have specified that managers who seek employees to be more committed and identify themselves with the organisation have to be sincere and create an atmosphere based on trust, whereas Arasli et al (2019) revealed that favouritism is related to the violation of the psychological contract and unsafe work climate.…”
Section: Discussionmentioning
confidence: 99%